2022
DOI: 10.1007/s10904-022-02442-6
|View full text |Cite
|
Sign up to set email alerts
|

Ferric Oxide Colloid: Towards Green Nano-Fertilizer for Tomato Plant with Enhanced Vegetative Growth and Immune Response Against Fusarium Wilt Disease

Abstract: Global food crisis due to climate change, pandemic COVID-19 outbreak, and Russia-Ukraine conflict leads to catastrophic consequences; almost 10 percent of the world’s population go to bed hungry daily. Narrative solution for green agriculture with high vegetation and crop yield is mandatory; novel nanomaterials can improve plant immunity and restrain plant diseases. Iron is fundamental nutrient element; it plays vital role in enzyme activity and RNA synthesis; furthermore it is involved in photosynthesis elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 85 publications
(78 reference statements)
2
20
0
Order By: Relevance
“…The disease symptoms were observed 45 days after sowing and the disease index and plant protection were assessed using a score consisting of five classes, as Spore germination (%) = Germinated spores Total spores × 100 described in Elbasuney et al (2022) with minor modifications;…”
Section: Disease Symptoms and Disease Indexmentioning
confidence: 99%
“…The disease symptoms were observed 45 days after sowing and the disease index and plant protection were assessed using a score consisting of five classes, as Spore germination (%) = Germinated spores Total spores × 100 described in Elbasuney et al (2022) with minor modifications;…”
Section: Disease Symptoms and Disease Indexmentioning
confidence: 99%
“…Plants can induce disease resistance to a group of pathogenic and non-pathogenic microorganisms to those plants or to varieties of them (Moisan et al 2019 ). Enhancement of plant resistance may be induced by biotic and abiotic elicitors (Farrag et al 2017 ; Omer et al 2022 ; Elbasuney et al 2022 ). The soil properties depending mainly on biological profile that can highly affect on plant growth and tolerance (Khalil et al 2015 ; Eid et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…ZnO NPs synthesized by emulsion, micro‐emulsion, and direct precipitation showed potent antimycotic activity against Penicillium and Mucor fungi 57 . Recent studies have shown the antifungal activity of ZnO NPs against Fusarium oxysporum with 100% growth inhibition on the 7th day with 2 mM concentration 58 . Antifungal activity of ZnO and ZnO NPs was evaluated on Fusarium oxysporum Schltdl (Nectriaceae) under laboratory and greenhouse conditions.…”
Section: Resultsmentioning
confidence: 99%
“…57 Recent studies have shown the antifungal activity of ZnO NPs against Fusarium oxysporum with 100% growth inhibition on the 7th day with 2 mM concentration. 58 Antifungal activity of ZnO and ZnO NPs was evaluated on Fusarium oxysporum Schltdl (Nectriaceae) under laboratory and greenhouse conditions. High concentrations of ZnO NPs from 1,600 to 3,000 ppm showed 81-83% growth inhibition of F.oxysporum.…”
Section: Antimycotic Analysismentioning
confidence: 99%